La retirada heterogénea: estrategias y desempeños de los grupos económicos nacionales en la Argentina de la década de 1990 - Castellani, Ana (2012)
This paper analyzes Argentinean business groups’ strategies and performance during the nineties. We find empirical evidence supporting the claims that: a) these strategies were diverse and changed over the decade; b) business groups’ specific strategies depended upon structural factors (such as sectorial specialization, linkages with the state, access to external markets, level of indebtedness and structure of corporate governance) as well as upon non structural factors (such as perceptions regarding market conditions and the timing and consolidation of economic reforms, and organizational dynamics); c) different strategies had heterogeneous impacts on business groups’ trajectories; and d) considering domestic business groups as a whole, it can be said that along the liberalization process they lost their previous position in the Argentinean economy and substantially changed their profile compared with precedent decades.